Social Media Addiction and Emotional Intelligence in Patients with Major Depressive Disorder - Ali İnaltekin; İbrahim Yağcı (AVES YAYINCILIK A.Ş., 2024)
The relationship between depression and severity of social media addiction is likely to be bidirectional. Nevertheless, current studies have addressed the depression score utilizing a scale in the general population instead of assessing this relationship in patients with major depressive disorder. Despite the fact that the negative relationship of social media addiction with emotional intelligence is acknowledged, the existence of this relationship in major depressive disorder has not been investigated yet. Hence, the objective of our study is to evaluate severity of social media addiction and emotional intelligence in major depressive disorder.This research was performed with 158 participants between the ages of 18 and 56 in Kars Harakani State Hospital Psychiatry Outpatient Clinic. Sociodemographic data form involving the age, gender, marital status, education level and employment status of the participants, Beck Depression Inventory, Bar-On Emotional Quotient Inventory, and Social Media Addiction Scale were implemented to the participants.Creating the group to be none-less addicted and medium-highly addicted with regard to the social media addiction scale score, it was observed that the emotional intelligence of the medium-highly addicted group was significantly lower, and the depression score was higher (P < .001). Furthermore, the severity of social media addiction had a positive relationship with the depression score and a negative relationship with the emotional intelligence score (r = 0.353, P < .001; r = -0.376, P < .001).Emotional intelligence in major depressive disorder is associated with both depression level and severity of social media addiction. Interventions, i.e., emotional intelligence skill training, might be practical for the aforementioned patients.
Keywords: Neurosciences. Biological psychiatry. Neuropsychiatry; Original Article; RC321-571